2021
DOI: 10.3390/plants10040779
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Characterization of By-Products of Habanero Pepper Grown in Two Different Types of Soils from Yucatán, Mexico

Abstract: By-products of edible plants may contain potentially useful phytochemicals. Herein, we valorized the by-products of Capsicum chinense by phytochemical characterization of its leaves, peduncles and stems. Plants of habanero pepper were grown in a greenhouse, in polyethylene bags with two soils that were named according to the Maya classification as: K’ankab lu’um (red soil) and Box lu’um (black soil). Habanero pepper by-products were dried using an oven, the extracts were obtained by Ultrasound Assisted Extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
(40 reference statements)
1
20
0
Order By: Relevance
“…Moreover, there was no significant difference between ABTS + value obtained by DES-UAE and W-UAE ( p > 0.05), whereas DES-UAE displayed significantly higher ABTS + value than other methods ( p < 0.05). These results indicated that DES-UAE was a high efficiency method compared with UAE coupled with traditional solvents (ultrapure water, 80% ethanol, and 70% methanol), which were usually used in the previous studies and showed a high efficiency for extracting polyphenols [27] , [32] , [33] , [34] , [35] , [30] , [36] . DES-UAE reportedly improved TFC and antioxidant capacity of Moringa oleifera L. leave extracts, compared with UAE coupled with traditional solvents [29] , [22] .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Moreover, there was no significant difference between ABTS + value obtained by DES-UAE and W-UAE ( p > 0.05), whereas DES-UAE displayed significantly higher ABTS + value than other methods ( p < 0.05). These results indicated that DES-UAE was a high efficiency method compared with UAE coupled with traditional solvents (ultrapure water, 80% ethanol, and 70% methanol), which were usually used in the previous studies and showed a high efficiency for extracting polyphenols [27] , [32] , [33] , [34] , [35] , [30] , [36] . DES-UAE reportedly improved TFC and antioxidant capacity of Moringa oleifera L. leave extracts, compared with UAE coupled with traditional solvents [29] , [22] .…”
Section: Resultsmentioning
confidence: 86%
“…The supernatant was obtained by centrifugation at 13,000 rpm for 10 min. The traditional solvents used were chosen based on previous studies [27] , [32] , [33] , [34] , [35] , which were efficient in polyphenolic extraction.…”
Section: Methodsmentioning
confidence: 99%
“…The column was an Acquity UPLC HSS C18 (100 A • , 1.8 µm, 2.1 mm × 50 mm) (Waters, Milford, MA, USA). Validation of the chromatographic method was carried in accordance with the Eurachem Guide: The Fitness for Purpose of Analytical Methods-A Laboratory Guide to Method Validation and Related Topics [49] reported in a previous work conducted by Chel-Guerrero et al [50]. Supplementary Materials Table S1 contains the validation values, as well as the chromatographic parameters of the method.…”
Section: Polyphenolic Determination By Uplc-dadmentioning
confidence: 99%
“…Analysis of metabolites (individual carotenoids and vitamins) was performed in an UPLC Acquity H Class (Waters, Milford, MA, USA) with a diode array detector and an Acquity UPLC HSS C18 column (100 Å, 1.8 µm, 2.1 × 50 mm) (Waters, Milford, MA, USA). Validation of the chromatographic methods was carried in accordance with the Eurachem Guide: The Fitness for Purpose of Analytical Methods-A Laboratory Guide to Method Validation and Related Topics [27] reported in a previous work conducted by Chel-Guerrero et al [28].…”
Section: Chromatographic Analysis Of Carotenoidsmentioning
confidence: 99%